Cut and Fill Volume Planning in the Green Harmony Warakas Housing Project Using a Nikon DTM 322 Total Station and Autocad Civil 3D Software - Dede Rukanda; Ervina Yuliyanti (Asosiasi Dosen Muda Indonesia, 2026)
Along with the increasing population growth, of course, the increase in needs will also increase significantly which will have an impact on the conversion of land functions into residential areas that are of course licensed and in accordance with government regulations. In this case, the Green Harmony Warakas housing developer as the land owner has plans to carry out development related to housing construction. However, in this housing development planning, the land that will be used for development has different heights so that it is necessary to plan the calculation of cut and fill volumes to determine which parts must be cut and filled in order to obtain a land surface in accordance with the previously planned plan. The problems that occur in the Green Harmony Warakas housing were chosen for research because they have problems related to cut and fill planning. The purpose of this research is to create a plan for calculating cut and fill volumes using AutoCAD Civil 3D software on the development land in the Green Harmony Warakas housing project. The cut and fill method is a method used to move excess material from one point to another with the aim of producing an even surface according to the existing plan. When planning cut and fill volume calculations, the required data is field measurement data, which will be processed into contour images. Then, calculations are performed based on the measurements to determine the volume of soil to be cut and filled.